Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi (Studi Empiris Pada Boys Bakery and Cake Sukoharjo) - Annisa' Amanattyas wahyudi Putri; Endang Masitoh; Purnama Siddi (Ekonomis: Journal of Economics and Business, 2021)
This study aims to examine and analyze the effect of user involvement, personal technical skills, top management support (organizational structure), formalization of system development and training and education programs on the performance of accounting information systems. Sources of data are primary data in the form of answers to angke and secondary data in the form of an overview of Boys Bakery and Cake. The method used in this study is the classical assumption test and multiple linear regression analysis with the help of the SPSS version 26 program. The population in this study was 74 people. The sample was selected from the purposive sampling method as many as 55 people from several sections and branches. The results of this study indicate that user involvement and training programs have an effect on the performance of the Accounting Information System while personal engineering skills, top management support (organizational structure), formalization of system development have no effect on the performance of the Accounting Information System.